Synchrotron FTIR and Raman spectroscopy provide unique spectral fingerprints for Arabidopsis floral stem vascular tissues. (8th November 2018) - Dinant, S; Wolff, N; De Marco, F; Vilaine, F; Gissot, L; Aubry, E; Sandt, C; Bellini, C; Le Hir, R
Abstract : Synchrotron radiation-based Fourier-transform infrared and Raman spectroscopy provide unique cell-specific spectral fingerprints for Arabidopsis floral stem vascular tissues, as demonstrated using SWEET mutants. Abstract: Cell walls are highly complex structures that are modified during plant growth and development. For example, the development of phloem and xylem vascular cells, which participate in the transport of sugars and water as well as providing support, can be influenced by cell-specific wall composition. Here, we used synchrotron radiation-based Fourier-transform infrared (SR-FTIR) and Raman spectroscopy to analyse the cell wall composition of floral stem vascular tissues of wild-type Arabidopsis and the double-mutant sweet11-1 sweet12-1, which has impaired sugar transport. The SR-FTIR spectra showed that in addition to modified xylem cell wall composition, phloem cell walls in the double-mutant line were characterized by modified hemicellulose composition. Combining Raman spectroscopy with a classification and regression tree (CART) method identified combinations of Raman shifts that could distinguish xylem vessels and fibers. In addition, the disruption of the SWEET11 and SWEET12 genes impacted on xylem wall composition in a cell-specific manner, with changes in hemicelluloses and cellulose observed at the xylem vessel interface. These results suggest that the facilitated transport of sugars by transporters that exist between vascular parenchyma cells and conducting cells is important in ensuring correct phloem and xylem cell wall composition.